2012
DOI: 10.4037/ajcc2012647
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Intolerance to Gastric Tube Feedings: A National Survey

Abstract: BackgroundConfusion about how to assess for intolerance to feedings often results in unnecessary feeding interruptions.ObjectivesTo report findings from a national survey of methods used by critical care nurses to assess tolerance to gastric tube feedings and to discuss the findings in light of current enteral nutrition guidelines.MethodsA pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 27 publications
(30 reference statements)
1
51
2
4
Order By: Relevance
“…The survey methods have been reported previously. 33 In summary, a pencil-and-paper survey was mailed to 1909 members of AACN who were certified as critical care nurses (CCRNs) and who worked in adult ICUs in university-based medical centers. In addition, readers of the AACN Critical Care Newsline (an electronic newsletter distributed to all AACN members each week) were asked to participate in the survey if they were registered nurses who worked in an adult intensive care area and had not already completed the mailed survey.…”
Section: Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey methods have been reported previously. 33 In summary, a pencil-and-paper survey was mailed to 1909 members of AACN who were certified as critical care nurses (CCRNs) and who worked in adult ICUs in university-based medical centers. In addition, readers of the AACN Critical Care Newsline (an electronic newsletter distributed to all AACN members each week) were asked to participate in the survey if they were registered nurses who worked in an adult intensive care area and had not already completed the mailed survey.…”
Section: Survey Methodsmentioning
confidence: 99%
“…As indicated in a previous report, 33 Which of the following bedside methods are advocated in your ICU to confirm that a feeding tube has remained in correct position AFTER feedings have been started? (Please mark all that apply.)…”
Section: Respondentsmentioning
confidence: 99%
“…Based on a survey among 2298 clinicians, Metheny et al 56 concluded that recommendations to obtain radiographic confirmation of the correct position for each feeding tube that is blindly inserted are not satisfactorily implemented. Instead and despite the recommendation to the contrary, auscultation is a widely used technique.…”
Section: Safety Issuesmentioning
confidence: 99%
“…55 A survey among American critical care nurses revealed that the most frequent thresholds used to interrupt enteral feeding were residual volumes of 200 or 250 mL. 56 Only 12.5% of nurses indicated that they allowed residual volumes up to 500 mL before interrupting feedings. Clearly, a need exists for the development and proper implementation of protocols based on current guidelines.…”
Section: Nutritionmentioning
confidence: 99%
“…7 Furthermore, the same population was surveyed about enteral feeding practices in 2010. 56 A survey link was posted on the AACN Facebook page on week 4 of our study. The volume of respondents increased by 153 (25%), suggesting that social media may be an effective recruitment tool for online surveys.…”
Section: Limitationsmentioning
confidence: 99%